Metal Catalyst to Construct Carbon Nanotubes Networks on Metal Oxide Microparticles towards Designing High‐Performance Electrode for High‐Voltage Lithium‐Ion Batteries. (24th March 2021) - Sun, Qujiang; Cao, Zhen; Zhang, Junli; Cheng, Haoran; Zhang, Jiao; Li, Qian; Ming, Hai; Liu, Gang; Ming, Jun
Abstract: Designing carbon nanotubes (CNTs)‐based materials are attracting great attention due to their fantastic properties and greater performance. Herein, a new CNTs network triggered by metal catalysts (e.g., Co, Ni, or Cu) is constructed on metal oxide (e.g., MnO) microparticles, giving rise to a high‐performance Co‐MnO@C‐CNTs anode in lithium‐ion batteries (LIBs). An extremely high capacity of 1050 mAh g −1, extraordinary rate capacities over 10 A g −1, and a long lifespan over 500 cycles are demonstrated. The great features of Co‐MnO@C‐CNTs anode are further confirmed in LIBs when the nickel‐rich cathode (e.g., LiNi0.8 Co0.1 Mn0.1 O2 ) is used and charged at a high voltage over 4.5 V. A high‐capacity retention of 71.5% can be maintained at 1 C over 150 cycles. The superior performance relates to the CNTs network, which not only acts as an "expressway network" for fast ion/electron transportation but also buffers structural variation. Moreover, the metal nanoparticles can also enhance the electrical conductivity and catalyze the (de‐)lithiation of metal oxide, resulting in higher reversibility and long‐term cyclability. This study opens a new avenue to prepare CNTs‐based functional materials and also explores the potential applications of metal oxide‐based anode for high‐performance batteries. Abstract : A new carbon nanotubes (CNTs)‐based material containing metal‐metal oxide@CNTs (e.g., Co‐MnO@C‐CNTs) is introduced, in which high performance is demonstrated in a high‐voltage lithium‐ion battery versus the nick‐rich layered oxide at 4.5 V. This presented strategy overcomes the challenges (i.e., severe capacity decay) of metal oxide anode applications in the lithium‐ion battery.